2021
DOI: 10.1111/ijd.15519
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer in non‐white liver transplant recipients: Mayo Clinic experience

Abstract: Background Limited data are available on the development of skin cancer and the associated risk factors for non‐White liver transplant (LT) recipients. The aim of this study is to determine the incidence of newly diagnosed skin cancer postoperatively and to identify the risk factors for the development of skin cancer in non‐White LT recipients. Methods We conducted an initial retrospective chart review of non‐White LT patients who received a transplant at our center between January 1, 2011, and December 31, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, the role of skin phototype in the NMSC risk for SOTRs remains unclear, as most published studies have included white patients only [ 7 , 8 , 9 ]. A recent study on 96 dark-skinned LTRs reported no NMSC to be detected during a 2-year follow-up, therefore suggesting a significantly lower risk for darker phototypes [ 10 ]. Moreover, in a large prospective study from Iannacone et al, typical NMSC risk factors (ethnicity, skin phototype, previous history of NMSC) were associated with NMSC occurrence after transplantation when considering both liver and kidney transplant recipients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of skin phototype in the NMSC risk for SOTRs remains unclear, as most published studies have included white patients only [ 7 , 8 , 9 ]. A recent study on 96 dark-skinned LTRs reported no NMSC to be detected during a 2-year follow-up, therefore suggesting a significantly lower risk for darker phototypes [ 10 ]. Moreover, in a large prospective study from Iannacone et al, typical NMSC risk factors (ethnicity, skin phototype, previous history of NMSC) were associated with NMSC occurrence after transplantation when considering both liver and kidney transplant recipients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study examining skin cancer in non-White liver transplant recipients at the Mayo Clinic supported the literature indicating that the incidence of de novo malignancy in these patients is low. [9][10][11] The aim of this study was to provide further information describing pre-and posttransplant characteristics and outcomes for patients who were non-White and developed skin cancer following the transplantation of any solid organ at the Mayo Clinic.…”
mentioning
confidence: 99%